Oriented CuCo2S4 nanograss arrays/Ni foam as an electrode for a high-performance all-solid-state supercapacitor. (23rd October 2017) - Wang, Yuqiao; Yang, Dawei; Zhou, Tianyue; Pan, Jie; Wei, Tao; Sun, Yueming
Abstract: An oriented nanograss array consisting of CuCo2 S4 nanocrystallines was directly prepared on Ni foam by a hydrothermal method. The uniform arrays with a single blade diameter of ∼100 nm and length of ∼4 μ m can grow tightly on Ni foam without any binders. The ordered one-dimensional structure facilitates the electron transport to Ni substrates along the axial direction. The electrochemical properties were presented in three- and two-electrode configurations, demonstrating an enhanced specific capacitance and a long-term cycling stability. As a practical all-solid-state device, it achieved a high energy density of 31.88 W h kg −1 at a power density of 3.20 kW kg −1 . Even at a higher power density of 15.23 W h kg −1, the device still had an energy density of 16.5 kW kg −1 . After 5000 cycles, the retention ratio was higher than 99% at high current density of 11.36 A g −1 .